Venezuela : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper describes economic developments in Venezuela during the 1990s. Economic conditions remained difficult in 1995. Continued problems in the banking system, higher public sector interest obligations, a decline in oil revenues, and deterioration in the non-oil fiscal balance kept the public finances under stress. The stance of monetary policy continued to be accommodating and interest rates remained negative in real terms. These policies, together with an increasingly misaligned fixed exchange rate and the maintenance of exchange controls, contributed to the further deterioration of private sector confidence.